A Model to Investigate Performance of Orthogonal Frequency Code Division Multiplexing - Nasaruddin Syafie; Melinda Melinda; Ellsa Fitria Sari (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
OFCDM is an attractive multiple access scheme for high data rate application in Fourth-generation (4G) wireless communication system. Previously, several researches were only investigated the performance of OFCDM based on variable spreading factor. However, there are several system parameters may affected the performance of OFCDM. Therefore, this paper investigates the impact of several parameters on the performance system of OFCDMA over Rayleigh Fading channel as a realistic channel in wireless communications.The simulation system model of OFCDM is introduced. The computer simulation is developed by using MATLAB programming in order to show the impact of several parameters for OFCDM’s performance including number of carriers, size of symbol, symbol rate, bit rate, size of guard interval and spreading factor. The simulation results show that the higher number of carriers, larger size of symbol, higher symbol rate, higher bit rate and larger spreading factor are giving the better system’s performance in terms of Bit Error Rate (BER). However, the larger guard interval is giving the worst system’s performance.So all the parameters should be considered in the implementation of OFCDM for the 4G wireless communication system. DOI: http://dx.doi.org/10.11591/telkomnika.v10i3.621